Toxigenic Diphtheriae Profile in Children in 2017-2018 - Siti Maemun; Aninda Dinar Widiantari; Nur Aliza; Masdalina Pane; Tri Yuli Setianingsih; Yeni Afrina; Farida Murtiani (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Corynebacterium diphteriae is divided based on its ability to produce toxin. Toxigenic C. diphteriae is the type that has capacity to produce toxin and life threatening. This study was descriptive study in Corynebacterium diphteriae found in children less than 18 years old who were administered to National Infection Center Prof. Dr. Sulianti Saroso. We found 36 viable toxigenic C. diphteriae isolates, which 52.8% intermedius strain, 33.3% gravis strain, 8.3% mitis, and 5.6% non-strain. Most of the host (52,8%) were 60-144 months years old. Majority of the host had completed basic vaccination recommended by Indonesian Paediatrician Association while 75% of them hadn’t gotten the supplementary doses. Fever (48.5%) and odynophagia (54.5%) were experienced by toxigenic intermedius strain infection. Snoring (50%) and thick pseudomembran mostly found in gravis strain host while Bullneck sign found in intermedius strain infection. Complications like airway obstruction, chronic kidney disease, and myocarditis were found in host with toxigenic intermedius strain by 66.7%, 100%, and 75%. Death case were also mostly with this strain. Intermedius strain were mostly found in this study. Complications and mortality were also connected to intermedius strain infection.